The Influence Of Bittersweet Chocolate Taste And Innovation On Buyback Decisions At Simetri Coffee Roasters Bekasi - Pradini, Gagih; Kusumaningrum, Anisa Putri; Meilida, Mutia Vella; Widodo, Wahyu Indro; Ariyanto (CV ODIS, 2023)
This study aims to: 1) know the influence of Taste on Repurchase at Simetri Coffee Roasters Bekasi, 2) know Product Innovation on Repurchase at Simetri Coffee Roasters Bekasi, 3) know Taste and Product Innovation together on Simetri Coffee Roasters Bekasi. This research uses quantitative methods. The number of samples in this study was 100 respondents. Respondents in the study were visitors to Simetri Coffee Roasters. The data collection techniques used are questionnaires and literature studies with data processing techniques using IBM SPSS version 26. The test results found that the Taste variable (X1) has an influence on Repurchase (Y) in Coffee Roasters Symmetry, the Product Innovation variable (X2) has an influence on Repurchase (Y) in Coffee Roasters Symmetry, and the Taste (X1) and Product Innovation (X2) variables simultaneously affect Repurchase in Simetru Coffee Roasters Bekasi with the results showing that this study has a positive and significant effect on Buyback (Y) in Simetri Coffe Roasters Bekasi.